First report of Bursaphelenchus mucronatus kolymensis (Nematoda: Aphelenchoididae) on Monochamus sutor (Coleoptera: Cerambycidae) in Spain. Issue 1 (29th September 2014) - Abelleira, A.; Ibarra, N.; Aguín, O.; Mosquera, P.; Abelleira‐Sanmartín, A.; Sorolla, A.; Ares, A.; Mansilla, P.; Balci, Y.
Summary This is the first report of Monochamus sutor as vector of B. mucronatus kolymensis, the European type of B. mucronatus (synonymous with B. kolymensis) in Spain. In 2013, a female of Monochamus sutor was caught in a Pinus sylvestris forest. Nematode species identification was based on morphological characteristics and on molecular and phylogenetic analysis of dauer juveniles and adults.